2004
DOI: 10.1207/s15328023top3104_8
|View full text |Cite
|
Sign up to set email alerts
|

Faculty Forum

Abstract: We surveyed recipients of Division Two's McKeachie Early Career Award, which is traditionally given to promising graduate student instructors of psychology. We found that most recipients work in academic settings after receiving the award. They have devoted the bulk of their academic careers to teaching and, to a lesser extent, research. Awardees' advice to graduate students and new faculty generally centered on viewing research and teaching as being compatible activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 65 publications
(89 reference statements)
0
3
0
Order By: Relevance
“…The researchers found that 428 of these concepts were mentioned in half of the glossaries, while only 33 concepts were dealt with in all glossaries. Griggs, Bujak-Johnson, and Proctor (2004) analyzed 44 textbooks and identified 155 concepts that were dealt with in 80 percent or more of the glossaries. In a different study (Nairn, Ellard, Scialfa, & Miller, 2003), six textbooks were examined.…”
Section: Core Concepts In Psychologymentioning
confidence: 99%
See 1 more Smart Citation
“…The researchers found that 428 of these concepts were mentioned in half of the glossaries, while only 33 concepts were dealt with in all glossaries. Griggs, Bujak-Johnson, and Proctor (2004) analyzed 44 textbooks and identified 155 concepts that were dealt with in 80 percent or more of the glossaries. In a different study (Nairn, Ellard, Scialfa, & Miller, 2003), six textbooks were examined.…”
Section: Core Concepts In Psychologymentioning
confidence: 99%
“…As a first step, a list of core concepts was created based on three studies (Griggs et al, 2004;Proctor & Williams, 2006;Zechmeister & Zechmeister, 2000). Only those concepts that were included in at least 50 percent of the examined textbooks were taken into account.…”
Section: Development Of the Testmentioning
confidence: 99%
“…There is a growing literature demonstrating that material from popular TV can be an effective component of undergraduate teaching, including psychology. For instance, Poonati and Amadio (2010) used examples from TV programmes to help students understand operant conditioning, while Eaton and Uskul (2004) used clips from The Simpsons to teach social psychology.…”
Section: The Ethics Of Reality Tvmentioning
confidence: 99%